Green Synthesis Nanopartikel Perak (NPAg) Menggunakan Ekstrak Etanol 96% Daun Kelor (Moringa oleifera) Sebagai Antibakteri - Viderika Haini Nurfadia; Anjas, Anjas Wilapangga; Sri Royani (The Journal Of Pharmacy, 2024)
Indonesia has various types of plants that can be used as medicine, one of which is moringa leaves (moringa oleifera). To utilize Indonesia's natural wealth, a method was developed in a drug delivery system that uses the principle of nanoparticles by utilizing medicinal plants as reductants. This study aims to prove that moringa leaf extract functions as a bioreductor and the synthesized silver nanoparticles have antibacterial potential. The nanoparticle synthesis method used in this study is the green synthesis method. Moringa leaves (Moringa oleifera) were extracted using the maceration method, then the 100 ppm concentration extract was used to synthesize silver nitrate (AgNO3). The silver nanoparticle solution was characterized using UV-Vis spectrophotometry and tested for antibacterial activity. An extract yield of 40.85% was obtained. The synthesis process of silver nanoparticles solution is brownish yellow in 6.56 seconds, has a wavelength of 400 nm with an absorbance value of 0.966. Antibacterial activity is indicated by the formation of a clear zone around the disc paper, silver nanoparticles showed an inhibition zone of 1.44 cm on petri dish 1 and 1.25 cm on petri dish 2. Based on the research that has been done, flavonoids in Moringa leaves are able to act as bioreductors in the synthesis of silver nanoparticles. In addition, the silver nanoparticles obtained have potential as antibacterial agents.